Análise socioambiental do entorno do estuário do Rio Cocó – Fortaleza / Ceará - Freires, Eduardo Viana; Gomes, Daniel Dantas Moreira; Sabadia, José Antonio Beltrão; Duarte, Cynthia Romariz; Souto, Michael Vendesteen Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The urban densification, which sued in the surroundings of the estuary of the Rio Cocó, favored by the huge population growth occurred in Fortaleza/CE/Brazil, in recent decades, involved in various negative impacts on site. In order to understand the environmental dynamics around the Poop River estuary, from the urban increment were conducted physical and human data collection in the area of interest through literature review, visit the field and analysis of satellite images. These data have been subjected to an integrated analysis that allowed understanding the socio-environmental framework in the area. The data collection in the field enabled the identification of various negative impacts promoted by urbanization in the study area, such as: filling of mangrove and wetland, deforestation, disposal and rubble in the riverbed, discharge of domestic sewage, silting, among others. The results point to the need for a systematic monitoring of urban expansion in the area; for identification and control of pollutant loads from residential and commercial; for the promotion of environmental education in the area; for the extension of effective police monitoring Cocó ecological park and its suitability to the national system of conservation Units as (SNUC) – Federal Law No. 9985 July 2000.